Emergency materials response framework for petrochemical enterprises based on multi-objective optimization. (15th April 2023) - Ye, Jihong; Jiang, Wei; Yang, Xinxiang; Hong, Bingyuan
Abstract: With the expansion of the scale of the petrochemical industry, the occurrence of safety production accidents has seriously affected people's livelihood and property. Many countries have developed emergency response systems for preventing and responding to kinds of accidents. In this paper, an emergency response framework whose mainly includes the configuration and management of emergency supplies is proposed by a multi-objective optimization method, considering pre-disaster and post-disaster stages. In the pre-accident stage, the configuration plan of emergency materials is obtained by solving the mathematical model according to the actual production of the enterprise. In the post-accident phase, based on the number of materials stored in the previous stage, third-party emergency forces are considered to optimize the delivery of materials by a multi-objective model. Finally, a petrochemical enterprise in Zhoushan, Zhejiang is taken as an example to illustrate the validity and practicability of the proposed framework. The framework can complete rescue work under the requirements of enterprise budget and rescue time, so as to reduce the safety and environmental impact caused by accidents, such as air pollution caused by fire accidents, marine pollution caused by leakage accidents, etc. In the analysis, all scheme in model can complete more than 80% of the commodity scheduling within half an hour, which is better than the actual situation of the enterprise. This study provides the way to reduce material utilization and promote cleaner production for sustainable supplies management in petrochemical enterprise. Highlights: A multi-objective method for emergency response of in petrochemical enterprise is proposed. The multi-objective framework including pre-disaster and post-disaster stages integrates costs and rescue time. Scheduling in the post-disaster stage considers the role of the third-party emergency force in the petrochemical. The model gives a variety of schemes that can be chosen, which are beneficial to economical and rescue time. A real-field case study is used to prove the practicality and advantages of the proposed method.